A tomada de decisão e sistemas de informação em saúde - Andre Queiroz de Andrade (2008)
In the last few years, the Brazilian healthcare environment has forced a change in the way organizations are managed. This is due to the rise in healthcare cost, with the appearance of new diagnostic techniques, and to the decentralization of public health initiatives. Therefore,the increase in decision-making efficiency and efficacy has become necessary for the survival of healthcare organizations. In this context, decision support systems are regarded as particularly suitable tools to promote improvements in the healthcare system. This dissertation intended to study the informational flow of NUPAD, as a healthcare organization. NUPAD, an UFMG department, is responsible for the coordination of neonatal screening in Minas Gerais State. The case study was directed by three questions: Which is the influence of information, organization and cognition on decision-making; Which is the best description for thedecision-making process that occur in the organization; How can we create an information systems for decision support in healthcare organizations. Organizational structure has important mechanisms of influence, through corporate governance rules and through sharing of cultural identity. The collaborative nature of decisions and the relevance of managers cognitive aspects in dealing with sensitive healththemes were also demonstrated. Finally, the study suggests that many descriptions of the decision-making processes are suitable to explain organizational decision, showing the complexity of managers job. Decision support systems should cover the collaborative aspectof decisions. Professionals that can bridge the needs of users, developers and the reality of healthcare organizations can decrease the probability of failures in the creation of such systems. The study ends with suggestions for new studies.